PENGARUH DEWAN KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2021 - Anggun Santika; Makhdalena Makhdalena; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to examine the influence of independent commissioners and audit committees on the financial performance of Islamic banking companies listed on the Indonesia Stock Exchange for the 2014-2021 period. The population in this study are all Islamic banking companies listed on the Indonesia Stock Exchange during the 2014-2021 period, namely 4 companies and all populations will be studied (census). The type of data used in this study is secondary data in the form of an annual report obtained from the website www.idx.com. The data analysis technique used to test the hypothesis is multiple regression analysis using SPSS 26 software. Based on the results of this study it shows that simultaneously the independent board of commissioners and audit committee variables have proven to have an effect on the financial performance of Islamic banking companies listed on the Indonesia Stock Exchange in the 2014-2014 period. 2021. Meanwhile, partially the independent board of commissioners and audit committee variables have no effect on the financial performance of Islamic banking companies listed on the Indonesia Stock Exchange for the 2014-2021 period.Key Words: Independent board of commissioners, Audit committee, Financial performance